Critical Literacy: A Universal Tool to Empower English Teachers and Learners - Subekti, Adaninggar Septi (Institut Hindu Dharma Negeri Denpasar, 2020)
Language teachers should not only facilitate learners to learn the language but also facilitate them to realize that every day’s discourses, including language and education, are socially constructed. This is where critical literacy (CL) plays its role as a frame through which teachers can actively and autonomously participate in the world around them and facilitate learners to be able to do so through learning instructions. CL functions as a universal tool, like bricoleur, one can use to see numerous social phenomena from a critical stance. It is a different way, lens, or teaching framework, believing that one should question every day’s discourses instead of just accepting them as they are, with the ultimate goal of promoting social justice. Hence, this paper explains the importance of CL in empowering both teachers and learners, how it works to serve this purpose, and some practical strategies of its implementation in a language class.